Historical and projected spatial and temporal rainfall status of Dar es Salaam, Tanzania, from 1982 to 2050 - Nyembo, Latifa O.; Mwabumba, Mohamed; Jahangeer, Jahangeer; Kumar, Vikram (Frontiers in Environmental Science, 2022)
Dar es Salaam city, like other cities in Africa, experiences flash floods during the rainfall season that destroy infrastructures due to the overflow of rivers and sewage blockage. This study investigates the historical and future variability and changes in spatial and temporal rainfall over Dar es Salaam. The station data and Climate Hazards Group Infrared Precipitation with Stations (CHIRPS) gridded data crossing 38 years (1982 – 2019) were used as baseline data and the CORDEX data set from 2021-2050 was used for projection under Representative Concentration Pathway (RCP4.5) forcing scenarios. Trend analysis of historical data has been carried out monthly, season and annual. Mann-Kendall statistical test and Sen's slope estimator were applied to identify the current trend direction and magnitude of change over time. A standardized anomaly index (SAI) was also employed to detect the region's wetness and dryness trend. The spatial distribution of rainfall in the city was investigated using Inverse Distance Weigh (IDW) technique. The statistical results reveal that a non-significant trend in rainfall was observed on monthly, seasonal and annual time scales. The variability of rainfall in the city was very highly noticed in many stations in which 55% of years in March-April-May (MAM), 43% October-November-December (OND) and 49% of annual rainfall was wet over the entire period. In the future, the annual circle of rainfall showed a slight decrease in monthly rainfall and an increase in the annual total with reference to historical rainfall. Also, the spatial distribution of the projected rainfall showed that the southern part of the city experienced higher rainfall than the other parts. The most significant findings obtained were the decrease of annual projected rainfall by 20%, MAM projected rainfall season by 42%, and increase of OND projected rainfall season by 38%. The finding of this study will be useful in the better management and planning of the city.